Network service orchestration in heterogeneous 5G networks using an open marketplace. Issue 6 (1st November 2017) - Bhat, Shireesh; Udechukwu, Robinson; Dutta, Rudra; Rouskas, George N.
Abstract : Network service orchestration across heterogeneous networks needs an open marketplace where the services advertised by the providers in different domains can be purchased for short‐term or long‐term time scales. The authors present two design paradigms and evaluate two corresponding prototypes which provide a framework for network services to be purchased. They compare the two prototypes from the point of view of how effective they are in addressing some of the challenges posed by heterogeneous 5G networks namely programmability, scalability and innovation. They present a network service orchestration algorithm which is advertised as a network service in the marketplace.